Investigating the Impact of Dari-Persian Language in Asia of Saghir (Turkey) - Habibdad Habib (RIRAI Publisher, 2023)
Given the greatness of ancient works in Dari-Persian, the viewer is very likely to imagine that all these works were written in the same region where Dari-Persian is predominant today. For this reason, the current research attempts a great attention to the historical territory of the Dari Persian language and should be recognized and relied on, which is more famous among other nations, but the place where it was produced was the place where the Dari Persian language has been closed and abandoned due to some reasons. Such a place that witnessed this event and where the known works belong is Asia Saghir (now Turkey). Centuries before today, Turkey was one of the major platforms for the rise of the Dari-Persian language. Dozens of books on philosophy, literature, medicine and poetry have been published, which can be found in the world`s prestigious libraries, even in some ancient buildings of Turkey. The method used in this study was qualitative approach with library techniques. Its basic sources are the books that are mostly written in connection with the study of Dari Persian language in Asia of Saghir.